1990
DOI: 10.1007/bf01176208
|View full text |Cite
|
Sign up to set email alerts
|

Representations of the self in social phobia: Vulnerability to social threat

Abstract: A revised Stroop color-naming task was used to test hypotheses derived from Beck's cognitive theory of anxiety disorders which proposes that social phobics are hypervigilant to social-evaluative threat cues. Color-naming latencies for social and physical threat words were compared to matched neutral words for both social phobics and individuals with panic disorder. As predicted, social phobics showed longer latencies for social threat words, and panickers had longer latencies for physical threat words. Latency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
169
2
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(194 citation statements)
references
References 25 publications
(26 reference statements)
15
169
2
8
Order By: Relevance
“…Mismatch between the color and content of the word (e.g., the word "green" printed in red) typically results in a longer response latency, which has been typically regarded as evidence of cognitive interference. Modified versions of Stroop tests presenting emotional threat words have been used to examine attentional biases in numerous conditions, including depression (Klieger & Cordner, 1990;Segal, Truchon, Gemar, & Guirguis, 1995;Segal & Vella, 1990), panic disorder (McNally et al, 1994;McNally, Riemann, & Kim, 1990;McNally, Riemann, Louro, Lukach, & Kim, 1992), obsessive-compulsive disorder (Foa, Ilai, McCarthy, Shoyer, & Murdock, 1993;Lavy, Vanoppen, & Vandenhout, 1994), posttraumatic stress disorder (Foa, Feske, Murdock, Kozak, & Mccarthy, 1991;Kaspi, McNally, & Amir, 1995;McNally, English, & Lipke, 1993), specific phobia (Lavy, Vandenhout, & Arntz, 1993;Mathews & Sebastian, 1993), and SAD (Becker, Rinck, Margraf, & Roth, 2001;Hope, Rapee, Heimberg, & Dombeck, 1990;Lundh & Ost, 1996;Maidenberg, Chen, Craske, Bohn, & Bystritsky, 1996;Mattia, Heimberg, & Hope, 1993;McNeil et al, 1995;Spector, response latencies to threat words in contrast with non-threat words have been deemed to indicate selective attention towards the threat.…”
Section: Emotional Stroop Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Mismatch between the color and content of the word (e.g., the word "green" printed in red) typically results in a longer response latency, which has been typically regarded as evidence of cognitive interference. Modified versions of Stroop tests presenting emotional threat words have been used to examine attentional biases in numerous conditions, including depression (Klieger & Cordner, 1990;Segal, Truchon, Gemar, & Guirguis, 1995;Segal & Vella, 1990), panic disorder (McNally et al, 1994;McNally, Riemann, & Kim, 1990;McNally, Riemann, Louro, Lukach, & Kim, 1992), obsessive-compulsive disorder (Foa, Ilai, McCarthy, Shoyer, & Murdock, 1993;Lavy, Vanoppen, & Vandenhout, 1994), posttraumatic stress disorder (Foa, Feske, Murdock, Kozak, & Mccarthy, 1991;Kaspi, McNally, & Amir, 1995;McNally, English, & Lipke, 1993), specific phobia (Lavy, Vandenhout, & Arntz, 1993;Mathews & Sebastian, 1993), and SAD (Becker, Rinck, Margraf, & Roth, 2001;Hope, Rapee, Heimberg, & Dombeck, 1990;Lundh & Ost, 1996;Maidenberg, Chen, Craske, Bohn, & Bystritsky, 1996;Mattia, Heimberg, & Hope, 1993;McNeil et al, 1995;Spector, response latencies to threat words in contrast with non-threat words have been deemed to indicate selective attention towards the threat.…”
Section: Emotional Stroop Testmentioning
confidence: 99%
“…They found that SAD patients displayed longer latencies specifically to social threat words, whereas GAD patients displayed longer latencies to all types of emotional words (Becker et al, 2001;Hope et al, 1990). McNeil and colleagues (1995) compared patients with circumscribed speech phobia, generalized SAD, and generalized SAD with avoidant personality disorder using an emotional Stroop test.…”
Section: Emotional Stroop Testmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, results of the modified Stroop procedure (Hope, Rapee, Heimberg, & Dombeck, 1990) have shown that subjects usually take longer to color-name fearrelated stimuli in comparison with their neutral counterparts. This study has demonstrated a novel behaviorally based approach to the assessment and effects of stimulus "meaning" on behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Stroop interference is obtained by selecting words relevant te tbe current concern of individuals and matching them with neutral words. Stroep interference has been feund in social phobia (Hope, Rapee, Heimberg, & Dombeck, 1990), panie disorder , generalized anxiety disorder (Mathews & MacLeed,[985), obsessive compulsive disorder (Fea & McNally, 1986), post-traumatic stress diserder (McNally, Kaspi, Rienmann, & Zeitiin, 1990), and spider pliebia (Watts, McKenna, Sharrock, & Trezise, 1986). In te fleld of eating diserders, several studies (Ben-Tovim & Walker, 1991;Ben-Tovim, Walker, Fok, & Yap, 1989;Channen, Hemsley, & de Silva, 1988;Ceoper & Fairburn, 1992;Cooper & Fairbum, 1993;Fairburn, Coeper, Coeper, McKenna, & Anastasiades, l991;Perpiflá, Hemsley, Treasure, & de Silva, 1993) have ebserved selective bias in the precessing of food-and body-related words in clinical samples, as welI as in dieters and restrained eatcrs (Ceoper & Fairbum 1992;Perpiñá et al, 1993;Stewart & Samoluk, 1997).…”
Section: Palabras Clave: Trastornos Alimentarios Sesgos Atencionalesmentioning
confidence: 99%